Analysis of Adverse Selection Behavior in Independent JKN Postpartum Participants - Solida, Adila; Ardiyansyah, Ardiyansyah (International Journal of Medicine and Health, 2025)
BPJS Health experienced losses due to stopped payment of contributions for participants who had utilized delivery services of more than 200 billion in a period of 2 years. It was recorded that 64.7% of mothers who were about to give birth registered as participants a month before giving birth and then stopped (43%) or behaved in adverse selection in payments after delivery. The largest percentage comes from independent participants or Non-Wage Recipient Participants (PBPU). In Jambi Province, non-compliance in paying BPJS Health contributions is highest in Jambi City. It was recorded that 77,489 participants were in arrears in 2021, resulting in losses of 60.1 billion. Non-compliance with paying contributions is adverse selection behavior. The aim of this study is to analyze the factors causing adverse selection behavior among independent participants in paying post-natal JKN contributions in Jambi City. Quantitative study approach with a cross-sectional design carried out in Jambi City. Respondents totaling 96 people were selected based on accidental sampling technique. The study instrument is a questionnaire. Data analysis consists of univariate analysis stages and bivariate analysis using the chi-square test. The study results found that as many as 33.3% of independent participants behaved in adverse selection when paying JKN contributions after giving birth. There is a significant relationship between the factors number of family members (p=0.001), knowledge (0.000), perception of illness (p=0.001), clinical assessment (p=0.000), and willingness to pay (WTP) with adverse selection behavior in independent JKN participants postpartum. It is recommended that BPJS Health consider implementing a waiting period method for participants who will utilize maternity services. As well as increasing promotive activities for the Jambi City Government in educating and increasing public awareness about the importance of health insurance in protecting household finances.